Relationship between external debt and economic growth in the West African Monetary Zone: A panel data analysis - Ismaila Jarju; Edward Nyarko; Kormay Adams; Ozolina Haffner; Olukayode S. Odeniran (West African Monetary Institute (WAMI), 2016)
This study analyzes trends and investigates the relationship between external debt and economic growth in the WAMZ using descriptive trend analysis and panel data analysis. The trend and descriptive analysis assessed the behavior of external debt and economic growth while the empirical analyses employed panel data regression in which a fixed effect model was estimated after the implementation of the Hausman test to verify its appropriateness over the random effect model. The fixed effect model and the dynamic version show that the relationship between external debt and growth in the WAMZ is non-linear "Laffer curve" shaped, confirming the debt overhang theory that the accumulation of external debt beyond a certain threshold adversely affects economic growth. The results also confirm the crowding-out effect of rising external debt stock as the co-efficient of external debt service was negative and statistically significant, indicating that rising debt service associated with high levels of external debt stock limits the use of limited resources (revenue) from being channeled to productive public investments that would accelerate economic growth.
Keywords: E60; B22; C33; R23; 330; External Debt; Economic Growth; Panel Data Analysis; WAMZ